2022
DOI: 10.3390/ijerph19052511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Natural Disasters on Mental Health: A Cross-Sectional Study Based on the 2014 China Family Panel Survey

Abstract: Mental health problems are a leading cause of disability in both developed and developing countries, and the consequences of mental health disorders for individuals, families, and society as a whole could be severe and costly. To supplement relevant research and provide insightful policy suggestions to families, government and societies, this study investigates the nexus between natural disasters and mental health for middle-aged and older adults in rural China. Based on data of 8721 observations from the 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…The main outcome variable in this paper is the mental health status of individuals in China. In order to evaluate individuals’ mental health more objectively and comprehensively, following existing studies [ 54 ], the mental health index is derived from the 6-item short form of the Center for Epidemiologic Studies of Depression (CES-D) in the CFPS. (CES-D questions: (1) In the past week, how many times have you felt down?…”
Section: Methodsmentioning
confidence: 99%
“…The main outcome variable in this paper is the mental health status of individuals in China. In order to evaluate individuals’ mental health more objectively and comprehensively, following existing studies [ 54 ], the mental health index is derived from the 6-item short form of the Center for Epidemiologic Studies of Depression (CES-D) in the CFPS. (CES-D questions: (1) In the past week, how many times have you felt down?…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable in this paper is the mental health status of individuals in China. In order to evaluate individual’s mental health more objectively and comprehensively, following existing studies ( Zhang et al, 2022 ), the mental health index is derived from the 6-item short form of the Center for Epidemiologic Studies of Depression (CES-D) in the CFPS. (CES-D questions: 1.…”
Section: Methodsmentioning
confidence: 99%
“…Natural disasters might impact rural household wealth through harming population health. For example, previous studies have found that natural disasters, such as typhoons, mudslides, and hailstorms, may adversely affect the physical health of individuals, sometimes causing death (Kahn, 2005;Han et al, 2021), and may also negatively affect individuals' mental health (Graham et al, 2019;Zhang et al, 2022). Residents need to spend time and money to improve ill health.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…Given that natural hazards affect residents' work and lives in different ways, many studies have examined the impact of natural disasters on individual and household economic behavior. Existing research found that natural disasters affect individuals' well-being (Rehdanz et al, 2015), investor sentiment (Hirshleifer and Shumway, 2003;Kamstra et al, 2003;Kaplanski and Levy, 2010), migration (Saldaña-Zorrilla and Sandberg, 2009;Warner and Afifi, 2014;Cattaneo and Peri, 2016;Pajaron and Vasquez, 2020), risk preferences (Bourdeau-Brien and Kryzanowski, 2020), mental health (Shultz, 2014;Graham et al, 2019;Zhang et al, 2022), and children's development (Rabassa et al, 2012;Deuchert and Felfe, 2015). Furthermore, studies have examined the impact of natural disasters on household income inequality (Yamamura, 2015;Abdullah et al, 2016;Keerthiratne and Tol, 2017), household savings (Filipski et al, 2019), household debt (Gallagher and Hartley, 2017), household consumption (Arndt et al, 2004;Wahdat, et al, 2021), and other household behaviors.…”
Section: Introductionmentioning
confidence: 99%